Integrating Islamic Values and AI-Based Deep Learning: Implementation at SMK Negeri 1 Kebumen Towards Achieving Educational SDGs - Chandra Intan Berliana; Siti Nurkhasanah; Purnomo; Dewi Rohmah (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to explore the implementation of Islamic values in conjunction with artificial intelligence (AI)-based deep learning at SMK Negeri 1 Kebumen as a strategic effort to support the achievement of Sustainable Development Goals (SDGs), particularly in the domain of inclusive and quality education. Theoretical framework: The research is grounded in an integrative theoretical framework that combines Islamic educational philosophy—centered on tauhid, akhlakul karimah, and ‘ilm nafi’—with modern pedagogical approaches, including Bloom’s Taxonomy and the Merdeka Curriculum. Literature review: The literature review highlights previous findings on the effectiveness of AI in improving student engagement and learning outcomes, while also acknowledging concerns regarding ethical dilemmas, digital dependency, and algorithmic bias. However, limited studies have addressed the intersection between AI, deep learning, and Islamic values in vocational education settings, especially in the context of Indonesian Islamic education. Methods: A qualitative descriptive method was used in this study. Data were collected through classroom observations, semi-structured interviews with four Islamic education teachers and nine students from different grade levels, as well as document analysis of teaching modules, digital infrastructure usage logs, and relevant budgeting records. This triangulated approach ensured a holistic understanding of the phenomenon under investigation. Results: Findings reveal that the integration of AI tools such as ChatGPT, Gemini, and virtual reality technologies significantly enhances student motivation, critical thinking, and participation in Islamic education classes. Lesson designs rooted in Bloom’s Taxonomy foster higher-order thinking skills, while AI tools help contextualize and personalize the learning experience. Nevertheless, the study also identifies potential risks, including over-reliance on AI, lack of ethical literacy, and challenges in maintaining Islamic identity in a tech-driven environment. Implications: This study has important implications for educators and policymakers, underscoring the need to implement AI-driven education within an ethical and religious framework. Novelty: The novelty of this research lies in its pioneering investigation of how Islamic values can guide and coexist with AI-based pedagogy to promote equitable and quality education aligned with global educational goals.